Value-based care in obstetrics: comparison between vaginal birth and caesarean section - Romulo Negrini; Raquel Domingues da Silva Ferreira; Daniela Zaros Guimarães (BMC, 2021)
Abstract Background Healthcare costs have substantially increased in recent years, threatening the population health. Obstetric care is a significant contributor to this scenario since it represents 20% of healthcare. The rate of cesarean sections (C-sections) has escalated worldwide. Evidence shows that cesarean delivery is not only more expensive, but it is also linked to poorer maternal and neonatal outcomes. This study assesses which type of delivery is associated with a higher healthcare value in low-risk pregnancies. Results A total of 9345 deliveries were analyzed. The C-section group had significantly worse rates of breastfeeding in the first hour after delivery (92.57% vs 88.43%, p < 0.001), a higher rate of intensive unit care (ICU) admission both for the mother and the newborn (0.8% vs 0.3%, p = 0.001; 6.7% vs 4.5%, p = 0.0078 respectively), and a higher average cost of hospitalization (BRL14,342.04 vs BRL12,230.03 considering mothers and babies). Conclusion Cesarean deliveries in low-risk pregnancies were associated with a lower value delivery because in addition to being more expensive, they had worse perinatal outcomes.